What ails tuberculosis notification from the private sector in urban India: a qualitative study among stakeholders in Bengaluru City, southern India - Meundi, Anand D.; Richardus, Jan Hendrik (Frontiers in Public Health, 2025)
BackgroundTuberculosis (TB) case reporting is vital for national and subnational surveillance and is mandated in India since 2012. All health providers, public and private, must report through the web-based system, “Nikshay.” The prevalence: notification ratio from 2019 to 2021 was 2.84 (prevalence was almost 3 times the notification), suggesting under-notification. This study explores the experiences, identifies barriers and facilitators, and examines perceptions regarding mandatory notification and incentives among private providers (PPs) in diverse contexts in Bengaluru city.MethodsFocused group discussions were held with specialist faculty of Pediatrics, Internal Medicine, and Pulmonology across three medical colleges and in-depth interviews included freelancing specialists and general practitioners. Data was collected in Bengaluru from January 2018 to July 2019, analyzed using a framework approach, referencing social learning theory, precede/proceed model, and theory of learned behavior. Thematic content analysis linked emerging themes to codes.ResultsThere was unmet expectation regarding lack of feedback from the NTEP regarding the patients notified. Emphasis on bacteriological diagnosis for every patient by NTEP deterred notification. Incentives were felt either to be insufficient for doctors or the PPs felt they were obliged to the national programme to notify. Barriers included obligation to maintain confidentiality, stigma, lack of knowledge of how to notify and facilitators included being recognized for their efforts and implementation of compulsory notification in letter and spirit.ConclusionStrategies to minimize stigma through education of patients at diagnosis and regular communication with private providers about the notification process, guidelines, and policy improvements can decrease resistance to notification. Recognizing best practices and rewarding on professional platforms could motivate private providers, alongside continued monetary incentives. Finally, demonstrating effective implementation of mandatory notification provision may boost private providers’ morale.